Jumps in commodity markets - Duc Binh Benno Nguyen; Marcel Prokopczuk; Chardin Wese Simen (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2017)
This paper investigates price jumps in commodity markets. We find that jumps are rare and extreme events but occur less frequently than in stock markets. Nonetheless, jump correlations across commodities can be high depending on the commodity sectors. Energy, metal and grains commodities show high jump correlations while jumps of meats and softs commodities are barely correlated. Looking at crossmarket correlations, we find that returns of commodities co-move with the stock market, while jumps can be diversified. Most commodities are strong hedges for U.S. Dollar returns but weak hedges for U.S. Dollar jumps. Most commodities act as both return and jump hedges for Treasury notes.
Keywords: G10; G11; G13; Q02; 330; Commodities; Jump Risk; Tail Risk; Hedge